Haplotypes in CCR5-CCR2, CCL3 and CCL5 are associated with natural resistance to HIV-1 infection in a Colombian cohort. (2023)
Variants in genes encoding for HIV-1 co-receptors and their natural ligands have been individually associated to natural resistance to HIV-1 infection. However, the simultaneous presence of these variants has been poorly studied.